Decompressive craniectomy in acute cerebral ischemia in rats - Engelhorn, Tobias; Heiland, Sabine; Schabitz, Wolf-Ruediger; Schwab, Stefan; Busch, Elmar; Forsting, Michael; Doerfler, Arnd (Neuroscience letters, 2004)
Early craniectomy has shown to reduce infarction size in experimental large MCA infarction probably due to improved leptomeningeal perfusion. Based on the hypothesis that craniectomy may also be beneficial in smaller MCA infarction we evaluated the effects of craniectomy on infarction size in small thromboembolic cerebral infarction in rats. Therefore, thromboembolic cerebral ischemia was induced in 40 rats by endovascular injection of autologous, fibrin-rich emboli. Twenty-one animals with a diffusion-weighted MR imaging (DWI)-derived infarction size of 50–100 mm 3 (involving one- to two-third of the MCA territory) at 1 h after injection were randomly assigned to two groups. Eleven animals of group 1 immediately underwent craniectomy, ten animals of group 2 (controls) were not treated. Serial DWI was performed at 4 and 24 h. Infarction size was assessed by TTC-staining at 48 h after emboli injection. As result, prior to treatment, at 1 h after emboli injection, infarction size in groups 1 and 2 was 65.9 ± 16.0 mm 3 and 67.9 ± 17.8 mm 3, respectively. At 4 and 24 h, infarction size in group 1 was 73.5 ± 22.1 mm 3 and 85.2 ± 24.7 mm 3, and 76.3 ± 21.0 mm 3 and 83.4 ± 22.9 mm 3 in group 2, respectively. TTC-derived infarction size was 84.0 ± 23.3 mm 3 and 82.7 ± 21.5 mm 3, respectively. There was no significant difference between the two groups ( P > 0.79). In conclusion, our results demonstrate that for small thromboembolic MCA infarction early craniectomy is not beneficial.